PAHs increase the production of extracellular vesicles both in vitro in endothelial cells and in vivo in urines from rats. (December 2019) - Le Goff, Manon; Lagadic-Gossmann, Dominique; Latour, Remi; Podechard, Normand; Grova, Nathalie; Gauffre, Fabienne; Chevance, Soizic; Burel, Agnès; Appenzeller, Brice M.R.; Ulmann, Lionel; Sergent, Odile; Le Ferrec, Eric
Abstract: Environmental contaminants, to which humans are widely exposed, cause or worsen several diseases, like cardiovascular diseases and cancers. Among these molecules, polycyclic aromatic hydrocarbons (PAHs) stand out since they are ubiquitous pollutants found in ambient air and diet. Because of their toxic effects, public Health agencies promote development of research studies aiming at increasing the knowledge about PAHs and the discovery of biomarkers of exposure and/or effects. Extracellular vesicles (EVs), including small extracellular vesicles (S-EVs or exosomes) and large extracellular vesicles (L-EVs or microvesicles), are delivery systems for multimolecular messages related to the nature and status of the originating cells. Because they are produced by all cells and detected within body fluids, EV releases could act as cell responses and thereby serve as biomarkers. To test whether EVs can serve as biomarkers of PAHs exposure, we evaluate the effects of these pollutants on EV production using an in vitro approach (human endothelial cell line, HMEC-1) and an in vivo approach (urine samples from PAHs-exposed rats). Our study indicates that, i) PAH exposure increases in vitro the EV production by endothelial cells and in vivo the release of EVs in urine, and that the stimulating effects of PAHs concern both S-EVs and L-EVs; ii) PAH exposure and more particularly exposure to B[a]P, can influence the composition of exosomes produced by endothelial cells; iii) the aryl hydrocarbon receptor, a cytosolic receptor associated to most deleterious effects of PAHs, would be involved in the PAH effects on the release of S-EVs, but not L-EVs. These results suggest that EVs may have utility for monitoring exposure to PAHs, and more particularly to B[a]P, considered as reference PAH, and to detect the related early cellular response prior to end-organ damages. Graphical abstract: Image 1 Highlights: B[a]P stimulates EV production by endothelial HMEC-1 cells. B[a]P stimulates production of both S-EVs (exosomes) and L-EVs (microvesicles). B[a]P modifies protein cargoes of S-EVs. S-EV, but not L-EV, increased production by B[a]P is AhR dependent. In vivo exposure to PAHs increases urinary EV amount. Abstract : Capsule: Exposure to polycyclic aromatic hydrocarbons, like benzo[a]pyrene, increases, in-vitro and in-vivo, production of exosomes and microvesicles and modifies their compositions.